Excessive All-Trans Retinoic Acid Inhibits Cell Proliferation Through Upregulated MicroRNA-4680-3p in Cultured Human Palate Cells - Yoshioka, Hiroki; Ramakrishnan, Sai Shankar; Shim, Junbo; Suzuki, Akiko; Iwata, Junichi (Frontiers in Cell and Developmental Biology, 2021)
Cleft palate is the second most common congenital birth defect, and both environmental and genetic factors are involved in the etiology of the disease. However, it remains largely unknown how environmental factors affect palate development. Our previous studies show that several microRNAs (miRs) suppress the expression of genes involved in cleft palate. Here we show that miR-4680-3p plays a crucial role in cleft palate pathogenesis. We found that all-trans retinoic acid (atRA) specifically induces miR-4680-3p in cultured human embryonic palatal mesenchymal (HEPM) cells. Overexpression of miR-4680-3p inhibited cell proliferation in a dose-dependent manner through the suppression of expression of ERBB2 and JADE1, which are known cleft palate-related genes. Importantly, a miR-4680-3p-specific inhibitor normalized cell proliferation and altered expression of ERBB2 and JADE1 in cells treated with atRA. Taken together, our results suggest that upregulation of miR-4680-3p induced by atRA may cause cleft palate through suppression of ERBB2 and JADE1. Thus, miRs may be potential targets for the prevention and diagnosis of cleft palate.